Studi Komparatif Triangular dan Quadrilateral Mesh pada Inversi Geolistrik 2D Wenner-Schlumberger untuk Zona High resistivity di Terowongan 11 Padalarang - Rudi Cahyadi; Widodo Widodo (Universitas Andalas, 2025)
This study aims to compare the results of 2D electrical resistivity inversion using triangular and quadrilateral mesh types in the Wenner–Schlumberger configuration to identify high-resistivity zones at Tunnel 11, Padalarang. Data acquisition was performed using 48 electrodes with a 10 m spacing and an ARES II multichannel resistivity meter. Data inversion was conducted with the ResIPy software employing two different mesh approaches. The results show that the triangular mesh produces smoother models, better adapts to topography, and achieves lower root mean square (RMS) errors (1.09–1.12%) compared to the quadrilateral mesh (4.67–4.72%). High-resistivity zones (>60 Ωm), interpreted as andesitic basalt, were identified at depths greater than 25 meters. The extent of these zones increases from Line 2 to Line 1, which has implications for blasting or drilling strategies during tunnel construction. These findings indicate that triangular mesh is more effective for complex geological conditions.